Predicting the defensive performance of individual players in one vs. one soccer games - Wilson, R. S.; Smith, N. M. A.; Pereira Santiago, P. R.; Camata, T.; de Paula Ramos, S.; Caetano, F. G.; Cunha, S. A.; Sandes de Souza, A. P.; Arruda Moura, F. (PLOS ONE, 2018)
The aim of this study was to use technical skill and physical performance and coaches` rankings to predict the defensive performance of junior soccer players. Twenty-one male players (mean age 17.2 years, SD = 1.1) were recruited from the Londrina Junior Team Football Academy in Brazil. Data were collected during regular training sessions. After participants had warmed up, players were asked to either dribble the ball or sprint through five custom circuits that varied in average curvature (0-1.37 radians.m-1). In addition, four coaches were asked to rank the players from best to worst in defensive ability. Dribbling, sprinting, and coaches` rankings were then compared with defending performance as assessed in the one vs. one competitions (N = 1090 paired-trials: 40-65 trials per individual), in which they acted as defender or attacker in turn. When defending, the objective was to steal the ball or prevent the attacker from running around them with the ball into a scoring zone. Testing occurred over three days. Overall, dribbling performance (r = 0.56; P = 0.008) and coaches` ranking (r = 0.59; P = 0.004) were significantly related to defensive ability; sprinting performance was not (r = 0.20; P = 0.38). Though dribbling performance and coaches` ranking each explained 30% and 37% of the variance in defensive performance, respectively, the two predictors were not related (r = 0.27; P = 0.23), so combined these traits explained more than half the variance in defensive performance. In conclusion, the current study demonstrates that including only one metric of closed-skill performance—dribbling speed—doubles the ability of coaches to identify their best defensive players in one vs. one scenarios.